Gusher : rock and roll as told by women. ([Chippendale, New South Wales] : [Gusher Magazine], 2016)
Gusher is an annual print magazine about rock music, written and created entirely by women and genderqueer creatives. Showcasing diverse voices in music journalism, Gusher aims to foster an intelligent and inclusive dialogue about rock music
Description based on: Issue 2 (December 2017).
Keywords: Rock musicians -- Periodicals; Rock musicians -- Anecdotes -- Periodicals; Rock music -- Periodicals